Effectiveness of a role-play simulation program involving the sbar technique: A quasi-experimental study. (June 2017) - Yu, Mi; Kang, Kyung ja
Abstract: Background: Accurate, skilled communication in handover is of high priority in maintaining patients' safety. Nursing students have few chances to practice nurse-to-doctor handover in clinical training, and some have little knowledge of what constitutes effective handover or lack confidence in conveying information. Objectives: This study aimed to develop a role-play simulation program involving the Situation, Background, Assessment, Recommendation technique for nurse-to-doctor handover; implement the program; and analyze its effects on situation, background, assessment, recommendation communication, communication clarity, handover confidence, and education satisfaction in nursing students. Design: Non-equivalent control-group pretest-posttest quasi-experimental. Participants: A convenience sample of 62 senior nursing students from two Korean universities. Method: The differences in SBAR communication, communication clarity, handover confidence, and education satisfaction between the control and intervention groups were measured before and after program participation. Results: The intervention group showed higher Situation, Background, Assessment, Recommendation communication scores ( t  = − 3.05, p  = 0.003); communication clarity scores in doctor notification scenarios ( t  = − 5.50, p  < 0.001); and Situation, Background, Assessment, Recommendation education satisfaction scores ( t  = − 4.94, p  < 0.001) relative to those of the control group. There was no significant difference in handover confidence between groups ( t  = − 1.97, p  = 0.054). Conclusions: The role-play simulation program developed in this study could be used to promote communication skills in nurse-to-doctor handover and cultivate communicative competence in nursing students. Highlights: SBAR communication scores differed significantly between groups. Communication clarity scores differed significantly between groups. SBAR education satisfaction scores differed significantly between groups. The intervention group's scores were higher relative to those of the control group. More attention should be paid towards role-play simulation using SBAR technique, to improve handover communication.